The Importance of Training and Development to Improve the Quality of Public Service: A Phenomenological Approach of Human Resources Performance at District Offices in Jakarta - Wahidin Septa Zahran; Diana Prihadini (Technium Social Sciences Journal, 2020)
The services provided to the community by local governments in general and district governments must be oriented towards the satisfaction of community services. One of the indicators in the public service is the ability of the officers to provide excellent services. If the community feels satisfied with the services provided by the district government officials, their performance will be considered good, and vice versa, if the community is not satisfied, the performance of the district government officials will be considered poor. In the provision of public services, especially those carried out at district offices, government agencies often face obstacles that cause people to be dissatisfied with the services they provide. This study aims at answering the questions of how the community perceive the service that they receive from the district staff, what obstacles are often encountered by the employees in terms of services at the district offices, and what efforts should be made by district institutions to improve the quality of public service. This study uses a phenomenological approach from a qualitative research design by applying semi structured interviews in data collection. The research proved that the competence of civil servants on public service can be improved through training and development program after conducting the Training Needs Analysis (TNA) so that the training can be conducted effectively and relevant to the employees’ needs. This study contributes significantly to the quality improvement of the government employees and the public service at the district level. In addition, the results of this study can be used as input for authorized institutions in the improvement of the human resources performance.